Treatment of Heart Failure in Real‐World Clinical Practice: Findings From the REFLECT‐HF Registry in Patients With NYHA Class II Symptoms and a Reduced Ejection Fraction. Issue 4 (2nd March 2015) - Böhm, Michael; Tschöpe, Carsten; Wirtz, Jost Henner; Lokies, Jan; Turgonyi, Eva; Bramlage, Peter; Lins, Katharina; Strunz, Anke M.; Tebbe, Ulrich
ABSTRACT Background Optimal medical therapy (OMT) for patients with chronic heart failure and a reduced ejection fraction (HF‐REF) includes angiotensin‐converting enzyme inhibitors/angiotensin receptor blockers, β‐blockers, and mineralocorticoid receptor antagonists, plus a diuretic. Hypothesis We hypothesized that OMT is less often prescribed in HF‐REF patients (≤35%) with New York Heart Association (NYHA) class II symptoms compared with those with NYHA class III/IV symptoms. Methods This was a cross‐sectional, observational, multicenter survey of hospital‐based cardiologists, office‐based cardiologists, and general practitioners in Germany. Results Out of a total of 384 patients enrolled, 144 had REF ≤35%. Patients with REF had NYHA class II symptoms in 39.6% (n = 57) and NYHA class III/IV symptoms in 60.4% (n = 87). The REF/NYHA class II group had a higher proportion of males than the REF/NYHA class III/IV group. For angiotensin‐converting enzyme inhibitors/angiotensin receptor blockers and β‐blockers, prescription rates were high and comparable between groups. However, prescription rates for mineralocorticoid receptor antagonists were lower compared with other guideline‐recommended treatments. Multivariate analyses indicated that OMT prescription was reduced for older patients and increased for patients cared for by an office‐based cardiologist. Conclusions Given the high proportion of patients with reduced left ventricular systolic function but only minor symptoms, HF‐REF appears to be underdiagnosed, and a higher proportion of patients than are currently recognized could potentially be candidates for OMT.